3-D frame behaviour and load rating of truss bridges in railway infrastructure. Issue 1 (10th November 2022) - Fu, Gongkang; Khademi, Faeze; Le, Hoat; Zoruba, Sergio
Abstract: Railway truss bridge load rating is studied herein using full scale diagnostic load test and 3-D finite element analysis which has not been typically practiced. Forty-eight bridges of Canadian National Railway are included, with eight load tested. One of the focuses is the effect of a collision strut member (CS) to the behaviour of main truss members, especially the end post L0U1. For simplicity, CS was ignored in design and past load rating using 2-D truss analysis. Its effect is identified herein for increased live load stress by inducing bending, leading to unconservative rating. In addition, these spans are found to behave more closely to frames. Out-of-plane bending of main truss members is also studied as part of 3-D behaviour. A multiplicative adjusting factor (AF) is accordingly developed and recommended as the realistic solution to enhance load rating by addressing bending previously ignored in truss models, for a large number of bridges in the infrastructure network. The findings of this study have been implemented in practice and can be useful for design and evaluation of truss bridges in North America and other continents for stress calculation in both strength and fatigue limit states, while localised stress analysis with fine mesh for connections was out of this study's scope.